In silico evaluation of bioactive compounds from the sea urchin Temnopleurus toreumaticus: Potential multifunctional agents against mosquito vectors and tropical pathogens - Karnan Ramachandran; Senthil Bakthavatchalam; Velavan Sivanandham; Shunmuga Vadivu Ramalingam; Pitchaimuthu Mariappan; Renganathan Senthil; Chandramohan Govindasamy; Khalid S. Al-Numair; Ramachandran Vinayagam; Zhi-Hong Wen; Hsien-Kuo Chin (PLoS ONE, 2026)
This study investigates the ethanolic extract of the sea urchin Temnopleurus toreumaticus (test and spine) for its larvicidal efficacy against Aedes aegypti , cytotoxicity, and in silico interactions supporting potential antimalarial and antiviral activities. Zoochemical profiling by Fourier-transform infrared spectroscopy (FT-IR) showed the presence of functional groups, while gas chromatography-mass spectrometry (GC-MS) analysis identified 24 bioactive compounds with insecticidal and enzyme-inhibitory properties. The extract exhibited strong larvicidal (LC₅₀ = 164.18 µg/mL) and pupicidal (LC₅₀ = 209.91 µg/mL) effects on A. aegypti in a concentration‑dependent manner, supported by significant acetylcholinesterase inhibition (IC₅₀ = 151.49 µg/mL). Morphological examinations showed epithelial disorganization and structural damage in treated larvae and pupae. In silico docking confirmed that the identified zoochemicals exhibited binding affinities ranging from –7 to –8 kcal/mol for juvenile hormone binding protein (PDB 5V13), –5 to –6 kcal/mol for acetylcholinesterase (PDB 1DX4), –4 to –5 kcal/mol for Plasmodium falciparum lactate dehydrogenase (PDB 1CEQ), and –4 to –5 kcal/mol for chikungunya nsP2 protease (PDB 3TRK), indicating their multitarget larvicidal, antimalarial, and antiviral potential. Yeast cell-based assays indicated cytotoxic activity (EC₅₀ = 159.27 µg/mL) with a strong dose-response relationship. Overall, the ethanolic extract of T. toreumaticus is a promising lead for next‑generation, environmentally safe biocontrol agents targeting vector‑borne diseases such as malaria and chikungunya, while clearly emphasizing that the antiviral and antimalarial properties are currently supported only by in silico evidence and require further in vitro and in vivo validation.